The protean presentations of XK disease (McLeod syndrome): a case series with new observations and updates on previously reported families - Walker, Ruth H.; Barreto, Mariana; Bateman, James R.; Bustamante, M. Leonor; Chiu, Graham; Feitell, Scott; Frey, Beat M.; Guerra, Patricio; Guerrero, Sofia; Jung, Hans H.; Maldonado, Fernando; Meyer, Eduardo; et al. (Frontiers in Neuroscience, 2024)
XK disease is a very rare, multi-system disease, which can present with a wide spectrum of symptoms. This disorder can also be identified pre-symptomatically with the incidental detection of serological abnormalities when typing erythrocytes in peripheral blood, or on other routine laboratory testing. Increasing awareness of this disorder and improved access to genetic testing are resulting in increasing identification of affected patients and families. Here we provide updates to some previously-reported families and patients and provide additional clinical details. We also report four new cases with a variety of presentations, one of whom had a novel mutation.